Exposure to febrile-range hyperthermia potentiates Wnt signalling and epithelial–mesenchymal transition gene expression in lung epithelium. (2nd January 2018) - Potla, Ratnakar; Tulapurkar, Mohan E.; Luzina, Irina G.; Atamas, Sergei P.; Singh, Ishwar S.; Hasday, Jeffrey D.
Abstract: Background: As environmental and body temperatures vary, lung epithelial cells experience temperatures significantly different from normal core temperature. Our previous studies in human lung epithelium showed that: (i) heat shock accelerates wound healing and activates profibrotic gene expression through heat shock factor-1 (HSF1); (ii) HSF1 is activated at febrile temperatures (38–41 °C) and (iii) hypothermia (32 °C) activates and hyperthermia (39.5 °C) reduces expression of a subset of miRNAs that target protein kinase-Cα (PKCα) and enhance proliferation. Methods: We analysed the effect of hypo- and hyperthermia exposure on Wnt signalling by exposing human small airway epithelial cells (SAECs) and HEK293T cells to 32, 37 or 39.5 °C for 24 h, then analysing Wnt-3a-induced epithelial–mesenchymal transition (EMT) gene expression by qRT-PCR and TOPFlash reporter plasmid activity. Effects of miRNA mimics and inhibitors and the HSF1 inhibitor, KNK437, were evaluated. Results: Exposure to 39.5 °C for 24 h increased subsequent Wnt-3a-induced EMT gene expression in SAECs and Wnt-3a-induced TOPFlash activity in HEK293T cells. Increased Wnt responsiveness was associated with HSF1 activation and blocked by KNK437. Overexpressing temperature-responsive miRNA mimics reduced Wnt responsiveness in 39.5 °C-exposed HEK293T cells, but inhibitors of the same miRNAs failed to restore Wnt responsiveness in 32 °C-exposed HEK293T cells. Conclusions: Wnt responsiveness, including expression of genes associated with EMT, increases after exposure to febrile-range temperature through an HSF1-dependent mechanism that is independent of previously identified temperature-dependent miRNAs. This process may be relevant to febrile fibrosing lung diseases, including the fibroproliferative phase of acute respiratory distress syndrome (ARDS) and exacerbations of idiopathic pulmonary fibrosis (IPF).